Learning in the Digital Age: Harnessing Decision Support Systems and Case Study for Physics Tutoring Program - Cecep Kustandi; Dheo Rimbano; Dikky Suryadi (STAI Hubbulwathan Duri, 2023)
In the contemporary educational landscape, the integration of Decision Support Systems (DSS), particularly the Simple Additive Weighting (SAW) method, offers a structured approach to evaluating teaching methods. This study focused on applying the SAW DSS in a Physics Tutoring Program. The results highlighted Interactive Simulations as the most effective teaching approach, emphasizing the role of technology in modern education. Hands-on Experiments and Group Discussions followed closely, underscoring the importance of experiential learning. Traditional Lectures, while foundational, benefit from enhanced interactivity. The SAW DSS's systematic approach ensures objective decision-making, though weight assignment can introduce subjectivity. A notable research gap emerged around the integration of SAW DSS with advanced educational technologies and its application across diverse cultural contexts. Future research avenues include refining the SAW method with real-time feedback and AI integration. In conclusion, as education evolves, tools like the SAW DSS provide invaluable insights, necessitating continuous adaptation to meet dynamic educational needs.